Informacijska pismenost v luči stalnih sprememb ali (ponovni) razmislek o informacijski pismenosti - Repinc, Urška (Šolska knjižnica, 2016)
An important pedagogical task of the school librarian is to contribute to an increase in information literacy, which he/she achieves in cooperation with other professional staff at the school. Innovation in the pedagogical process requires continuous reflection on the concept of information literacy, especially on its incorporation into school work. Pedagogical work that includes guided inquiry contributes to the students learning how to learn and how to increase the effect of their learning.
Keywords: holistični pristop; informacijska pismenost; sodelovanje; šolske knjižnice; trajnostni razvoj; vodeno poizvedovanje